Windshield Damage Analysis on ATR 42/72-600 Aircraft at PT. DEF - Wilarso, Wilarso; Indra Gumilar; Hilman Sholih; Asep Saepudin (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2025)
Windshield damage on ATR 42/72-600 aircraft at PT. DEF has caused operational disruptions, including flight delays, increased maintenance costs, and potential safety risks. Repeated damage to the Windshield is caused by various factors, namely inspection and maintenance errors, improper installation procedures, damage to the heating system or pressure distribution, glass material degradation, and exposure to extreme weather and UV rays. In this study, the analysis was carried out using a quantitative method with a fishbone diagram to identify the main causes of damage and appropriate mitigation steps. The results of the analysis showed that the main factors contributing to the damage were errors in inspection, installation errors, and material degradation. After implementing mitigation steps such as improving technician training, revising maintenance procedures, and improving material selection, there was a significant decrease in the frequency of Windshield damage. An indication of the success of these mitigation steps can be seen from the repairs carried out during January to June 2024 which succeeded in reducing damage and rejects on the Windshield by 40% compared to 2023, improving the quality of maintenance, inspection and material durability. In terms of maintenance costs for spare parts, there is a decrease in spending on purchasing spare windshields, namely USD 15,375 (PPG Inc.) x 10 units = USD 153,750 in 2023 to USD 21,915 (Saint Gobain) x 3 units = USD 65,745 in 2024 (June), which is 42% until mid-2024. This step increases operational reliability, cost efficiency, flight safety, and employee productivity, customer satisfaction also increases along with reduced flight delays and cancellations due to technical problems. Overall, the study succeeded in reducing Windshield damage and increasing the company's operational efficiency and reliability